(untitled) (Research, Society and Development, 2022)
Ludwig’s angina is an infection of the submandibular space. It is a polymicrobial reserve that reflects an oral microbiological flora. The most common cause is extension of infected lower molar teeth. Airway occlusion and spread of infection in the mediastinum are complications of greater clinical importance, due to their severity. Given the above, this study reviewed Luwig’s angina, highlighting the diagnostic methods, the complications that can occur from an objective. For the construction of this article, a bibliographic survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, using the Mendeley reference manager. Known disease is a known and little known disease that can be fatal Ludwig. This infection can often be harmed and this can have dangerous consequences for the patient’s life. A can be prevented by timely interventions and periodic care, which can prevent odontogenic infections. In the case of Ludwig’s angina, early diagnosis is essential to save the patient’s life. After initial antibiotic therapy and once the patient’s life is no longer at risk, adequate endodontic therapy can be considered a valid therapy for this disease.